A Sustainable Green IT Model for Organisations of Pakistan (SGITMOP) - Pervaiz, Sumaiya (Curtin University, 2025)
IT products have an impact on developing countries, it is becoming increasingly clear that green IT practices should be prioritised by academics and practitioners. Therefore, a sustainable Green IT model for organisations in Pakistan (SGITMOP) is derived from a mixed-methods approach based on eight factors identified in the literature review. In this research, a SGITMOP develops to minimise the negative impacts of IT usage in alignment with Pakistan's vision of achieving environmental sustainability by 2030.